Kontekstualisasi Fikih Sosial Piagam Madinah dalam Kehidupan Berbangsa di Indonesia Perspektif K.H. Taufiqul Hakim - Albar Waritsul Fuqoha Albar; Arinal Haq Zakiyyat (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2026)
This study examines the contextualization of social fiqh values contained in the Medina Charter within Indonesian national life from the perspective of K.H. Taufiqul Hakim. This research is important amid increasing challenges of intolerance, religious radicalism, and social polarization in Indonesia’s multicultural society. The study aims to analyze the social fiqh principles in the Medina Charter and explain their relevance to contemporary Indonesian society through the socio-religious thought of K.H. Taufiqul Hakim. This research employs a qualitative descriptive method based on library the research using normative, biographical, and social fiqh approaches to analyze research objects. Primary data were obtained from the Medina Charter, the book Mīthāq al-Madīnah: Pancasila dan Piagam Madinah Dasar Kehidupan Berbangsa dan Bernegara, other works of K.H. Taufiqul Hakim, and pesantren documentation. Secondary data were collected from fiqh siyāsah literature, social fiqh books, journals, and related scientific works. The findings reveal that the Medina Charter contains strong social fiqh values, including justice, tolerance, social solidarity, deliberation, and protection of citizens’ rights. K.H. Taufiqul Hakim contextualizes these values through the concepts of religious moderation, nationalism, social harmony, and pesantren-based moral education. This study implies that social fiqh can serve as a paradigm for strengthening national harmony and developing inclusive Islamic thought in contemporary Indonesia.